COMPARATIVE EVALUATION OF CHEMICAL, PHYSICAL PROPERTIES AND HEAVY METALS IN SOIL UNDER COCOA, CASSAVA FARM AND UNCULTIVATED LAND - Dania, S.O.; Ilekporia, E.O.; Olamide, R. (Journal CleanWAS)
The comparative evaluation of the chemical, physical properties and heavy metals present in soil under Cocoa, Cassava and uncultivated land was carried out in Ambrose Alli University, Ekpoma. Soil samples from the top soil (0cm – 15cm) were collected with an auger from cocoa, cassava farms and uncultivated land at Iruekpen, Edo State for analyses. The soil was air dried, sieved and the sieved soil samples were analyzed for its texture, aggregate stability, chemical properties and heavy metals. The results indicated that Sand fraction in Cocoa plantation was higher than that of Cassava and Uncultivated land. The silt and clay fraction was higher in cassava farm than the other land use and the textural classes of the soils were loamy sand. The percentage of soil Aggregate Stability under cocoa plantation was 12% and was significantly (p≤0.05) higher compared to others. The organic carbon and nitrogen content and the heavy metals concentration such as copper, manganese were significantly (P≤0.05) higher in cocoa farm compared to other land use. The findings of the study provide valuable insights into the relationship between physical and chemical soil properties with land use practices. In conclusion, the different land use significantly influences the aggregate stability, chemical, physical properties and the heavy metals content of the soil.